Degradation of Norfloxacin in an Aqueous Solution by the Nanoscale Zero-Valent Iron-Activated Persulfate Process. (1st September 2020) - Zhang, Yanchang; Zhao, Lin; Yang, Yongkui; Sun, Peizhe
Abstract : In this study, nanoscale zero-valent iron (nZVI) was synthesized and used to activate persulfate (PS) for the degradation of norfloxacin (NOR). The nZVI/PS system exhibited a high reactivity towards NOR, and the degradation efficiency of NOR (100 mg/L) reached 93.8% with 0.1 g/L nZVI, 12 mM PS, and an initial pH of 7.0 within 7 min. The NOR degradation followed a pseudo-first-order kinetic model, and the effects of parameters such as nZVI dosage, PS concentration, initial pH, and temperature were investigated systematically. Overloading of nZVI lowered the degradation efficiency owing to the quenching effect of excessive Fe 2+ . The higher PS concentration and temperature favored the degradation of NOR. The influence of pH was not obvious, and the degradation was effective in a wide pH range. In addition, the radical quenching experiments and electron paramagnetic resonance (EPR) indicated that both sulfate radical (SO4 ⋅- ) and hydroxyl radical (OH ⋅ ) were the dominant radicals in the degradation process, in which the latter played a more important role. Finally, three degradation pathways were proposed based on the result of intermediates identified by liquid chromatography-mass spectrometry. Overall, this study indicated that the nZVI/PS system could provide a promising alternative for NOR wastewater treatment.